The Arts of Thailand A Handbook of the Architecture, Sculpture, and Painting of Thailand (Siam), and a Catalogue of the Exhibition in the United States in 1960-61-62 - Bowie, Theodore (Indiana University Press, 1961)
The first accessible text of its kind ever published in America, this richly illustrated book presents a comprehensive history of Thai architecture and sculpture from the 6th through the 20th centuries written by Alexander B. Griswold, a noted authority on Siamese art, and a commentary on Thai painting by Elizabeth Lyons. 163 beautifully reproduced halftones and a full color plate depict the astonishing variety of Thai museum pieces, sites, and monuments. Also included are an archeological map and full catalog notes on the objects in the Exhibition of the Arts of Thailand circulating in the United States in 1960-1962, prepared by M. C. Subhadradis Diskul, Chief Curator of the National Museum of Bangkok.